Risk Factors of Central Lymph Node Metastasis in Papillary Thyroid Microcarcinoma and the Value of Sentinel Lymph Node Biopsy - Zhao, Jing; Zhao, Ye; Ling, Yuwei; Kang, Hua (Frontiers in Surgery, 2021)
Objective: The present study aims to investigate the risk factors of central lymph node metastasis (CNM) in papillary thyroid microcarcinoma (PTMC) and evaluate the predictive value of sentinel lymph node biopsy (SLNB) during surgery. Methods: The clinicopathological data of 179 patients with PTMC staging in cN0 and performed SLNB was analyzed retrospectively. Positive sentinel lymph node ratio (PSLNR) and additional positive lymph nodes (APLN) were analysed in cases with positive SLNB. The efficiency of SLNB was investigated. ROC curves were plotted to evaluate the predictive value of PSLNR for APLN. Results: Cumulative maximum diameter of tumors (CMD) (P=0.041) and capsule involvement (CI) (P=0.014) were independent risk factors for central lymph node metastasis. The SLNB success rate was 97.28%, the incidence of CNM was 31.28%. The sensitivity, specificity, false positive rate (FPR), false negative rate (FNR), positive predictive value (PPV) and negative predictive value (NPV) of SLNB to evaluate CNM and APLN were 82.14 vs. 61.54%, 100 vs. 80.39%, 0 vs. 19.61%, 17.86 vs. 38.46%, 100 vs. 34.78%, and 92.48 vs. 92.48%, respectively. For cases with positive SLNB, subgroup analysis was performed according to APLN. The PSLNRs of true and false positive groups were 0.4620±0.1744 and 0.2425±0.1355 respectively (P<0.001). Analyzing the predictive value of PSLNR by ROC curve, the optimal diagnostic cut-off point was 0.2917 (AUC=0.861 [CI:0.757, 0.966], P＜0.001), and the sensitivity, specificity, FPR, FNR, PPV, and NPV of PSLNR were 87.50%, 73.33%, 26.67%, 12.50%, 63.64%, and 91.67% respectively. Conclusion: CMD and CI are independent risk factors for central lymph node metastasis in PTMC. SLNB has good predictive value for CNM. For cases with positive SLNB, PSLNR could be used to predict the presence of APLN, which may provide a theoretical basis for intraoperative lymph node dissection.